New functions of DDR1 collagen receptor in tumor dormancy, immune exclusion and therapeutic resistance - Sirvent, Audrey; Espie, Kevin; Papadopoulou, Evangelia; Naim, Dana; Roche, Serge (Frontiers in Oncology, 2022)
The tumor microenvironment facilitates cancer progression and therapeutic resistance. Tumor collagens and their architecture play an essential role in this process. However, little is known about the mechanisms by which tumor cells sense and respond to this extracellular matrix environment. Recently, the Discoidin Domain Receptor 1 (DDR1), a collagen receptor and tyrosine kinase has emerged as an important player in this malignant process, although the underlying signaling mechanisms remain unclear. Here, we review new DDR1 functions in tumor dormancy following dissemination, immune exclusion and therapeutic resistance induced by stromal collagens deposition. We also discuss the signaling mechanisms behind these tumor activities and the therapeutic strategies aiming at targeting these collagens-dependent tumor responses.